A temporal ambidexterity view towards emerging market firms - Wang, S.; Luo, Yadong; Celly, N.; Sun, J. (2014)
In this paper, we present a temporal ambidexterity view to theorize how firms operating in emerging markets improve their performance over time. Specifically, we conceptualize that temporal ambidexterity, a firm's mega-capability to deliberately and dynamically orchestrate its short-term and long-term pursuits, serves as a key enabler for the firm to thrive in emerging markets. We explain that emerging markets serve as a unique context that provides firms with a large array of opportunities, with some more future oriented, because much needed institutional and industry support to materialize these opportunities is lacking. Thus firms that are temporally ambidextrous will prosper over time and enjoy greater performance improvement. We operationalize temporal ambidexterity as a multidimensional construct, specified by the simultaneity, intensity, and symmetry (or the S-I-S criteria) of firms' pursuits of short-term stability and long-term growth. We hypothesize that firms cultivate temporal ambidexterity through developing appropriate organizational mechanisms (i.e., orientation, governance, and capabilities). Specifically, firms equipped with stronger orientation in analysis and adaptation, with stronger outcome-based top management governance and frontline employee autonomy delegation, and featured with stronger combinative capabilities and harmonious culture will be more temporally ambidextrous.